2012
DOI: 10.3390/rs4020354
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Sensor Comparison between THEOS and Landsat 5 TM Data in a Study of Two Crops Related to Biofuel in Thailand

Abstract: Knowledge of the spatial distribution of biofuel crops is an important criterion to determine the sustainability of biofuel energy production. Remotely sensed image analysis is a proven and effective tool for describing the spatial distribution of crops using vegetation characteristics. Increases in the number of options and availability of satellite sensors have expanded the horizon of choices of imagery sources for appropriate image acquisitions. The Thailand Earth Observation System (THEOS) satellite is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The results showed that the reflectance and NDVI of Landsat-8 were both greater than those of Landsat-7. In order to accurately distinguish cassava and sugarcane in images, Phongaksorn et al [33] compared the reflectance and NDVI of Landsat-5 and THEOS. The results showed that THEOS can better distinguish the two crops.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the reflectance and NDVI of Landsat-8 were both greater than those of Landsat-7. In order to accurately distinguish cassava and sugarcane in images, Phongaksorn et al [33] compared the reflectance and NDVI of Landsat-5 and THEOS. The results showed that THEOS can better distinguish the two crops.…”
Section: Introductionmentioning
confidence: 99%
“…Phongaksorn et al (2012), using the Landsat-/TM satellite in a sugarcane area in Thailand, obtained a KI of 0.92. Silva Junior et al (2013) made an automatic detection of fires in sugarcane plantations and obtained the best result (KI = 0.90) with the Maxver classification with the treatment of radiometric correction.…”
Section: Resultsmentioning
confidence: 99%
“…The supervised classification method of Maximum Likelihood (Maxver) was used to map sugarcane areas, following the example of other studies (Phongaksorn et al, 2012;Silva Junior et al, 2013;Mulianga et al, 2015). This algorithm makes the 'pixel-to-pixel' classification of the images, using the multispectral information of each pixel obtained in previously acquired training samples to find homogeneous regions (classes).…”
Section: Methodsmentioning
confidence: 99%